Iowa RBA, July 15, 1996 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1996)
Iowa RBA update for July 15, 1996. Highlights of the update include sightings of Red Crossbills, a Prairie Wabler, a White-faced Ibis, a Mississippi Kite, and the continued presence of a Black-headed Gull. Also of note were observations of numerous species of shorebirds at Rathbun Lake and near Lake View. Also included are handwritten notes for the next week's update with sightings of an American Avocet and a Trumpeter Swan. Epson - sheet feed/flatbed